Systemic delivery of biopharmaceuticals: parenteral forever? - Grenha, Ana (2013)
The subject of systemic delivery of biopharmaceuticals has been discussed in some occasions in Journal of Pharmacy and Bioallied Sciences, which is now in its 11th issue. The last decades have witnessed a strong biotechnological progress, making available many biopharmaceuticals with great therapeutic potential, in many cases promising an undisputed place alongside other established therapies. The meaning of biopharmaceuticals is sometimes misleading but, rigorously, this word refers to therapeutic molecules that are biological in nature and manufactured using biotechnology. In this sense, a considerable wide variety of macromolecules is included in this group, from proteins and peptides, to antigens and nucleic acids. Their administration is extremely challenging because of biopharmaceutical and physicochemical limitations, requiring circumventing enzymatic degradation and reducing immune reactions, while ensuring molecular stability and permeability. Parenteral administration appears in this context as an obvious option, as it overcomes some of the referred issues. Actually, to date, the vast majority of marketed biopharmaceuticals is administered by direct injection, usually through intravenous, subcutaneous or intramuscular route. However, the associated cost and patient discomfort, have turned the research efforts of both industrial and academic partners towards alternative possibilities that increase patient compliance.